Software defined networking approach for efficient information dissemination in vehicular networks - Kalupahana Liyanage, Kushan Sudheera (Nanyang Technological University, 2020)
Vehicular Ad-hoc Networks (VANET) have emerged as a viable solution for the network related problems in Intelligent Transportation Systems (ITSs). However, with its current architecture, especially with the unavailability of the global network information, VANET has not been able to fulfill some of the necessities for efficient information dissemination and most critically, still lacks flexibility and programmability. Recently, Software Defined Networking (SDN) has been introduced into the vehicular domain in order to overcome the shortcomings in VANET. SDN is capable of handling the dynamic nature of networks with intelligent applications while lowering operational costs through simplified hardware and software. Yet, the architectural limitations of the presented Software Defined Vehicular Networks (SDVN), especially the centralization of control plane and its placement, have imposed doubts on its usability especially in the midst of stringent delay requirement of VANET applications.